2017
DOI: 10.5296/ijld.v7i3.10926
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service Climate and Job Satisfaction on Service Quality in a Higher Education Platform

Abstract: This study examines service climate and service quality through the mediating impact of job satisfaction within a tertiary education level in Bangladesh. The sample size of the study consisted of 140 faculty-members from four different private universities of Dhaka city and a structured questionnaire was designed to assess the service quality of higher education. Several statistical methods such as t-test, correlations and multiple-regression were used to analyze the data. The study discloses that the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…This means that BPO workers viewed their physical working environment as visually appealing and is generally congruent to the services being provided (Eberendu, Akpan, Ubani, and Ahaiwe, 2018). These findings agree with the study of Osman (2017) that highly satisfied employees tend to be more enthusiastic to participate with positive and helpful attitudes that lead to superior services. While Timney (2017) argued that loss of customer goodwill may also occur during the first transaction by means of giving wrong information, it is safe to say that BPO workers are quite competent in terms of giving correct services and handling customers with courtesy and enthusiasm.…”
Section: Service Performance Of Bpo Workers In Davao Citysupporting
confidence: 91%
See 1 more Smart Citation
“…This means that BPO workers viewed their physical working environment as visually appealing and is generally congruent to the services being provided (Eberendu, Akpan, Ubani, and Ahaiwe, 2018). These findings agree with the study of Osman (2017) that highly satisfied employees tend to be more enthusiastic to participate with positive and helpful attitudes that lead to superior services. While Timney (2017) argued that loss of customer goodwill may also occur during the first transaction by means of giving wrong information, it is safe to say that BPO workers are quite competent in terms of giving correct services and handling customers with courtesy and enthusiasm.…”
Section: Service Performance Of Bpo Workers In Davao Citysupporting
confidence: 91%
“…Through various quality assurance metrics, call centers can monitor employees' service performance and customer satisfaction rates. It is found that highly satisfied employees are more enthusiastic and positive in dealing with customers, leading to superior services (Osman, 2017). This is parallel to the study of Godarzvand et al (2016), which reveals that job satisfaction leads to employees' effective participation, which in turn significantly affects their service performance.…”
Section: Service Performancesupporting
confidence: 69%
“…In the same manner, Vaseer and Shahzad (2016) emphasized the importance of the relationship between job satisfaction and service quality and found a strong effect of the former on the latter in public and private universities in Pakistan. In addition, Osman et al(2017) found that the job satisfaction of faculty members partially mediated the relationship between service climate and service quality. In a systematic review that evaluated the service quality of higher education institutions from a post-COVID-19 perspective Camilleri (2021) discovered that attitudes and behaviors influenced employees' ability to provide appropriate service quality in the higher education context.…”
Section: Literature Reviewmentioning
confidence: 97%
“…A similar study emphasized the vital effect of JS on SQ; the study found a significant impact of JS on SQ in the universities in Pakistan [3]. Another study found that faculty satisfaction partially mediates the service climate and service quality relationship [48]. A recent systematic review of the service quality in the post-COVID-19 era in higher education institutions by [49] found that employee attitudes and behaviors have a major effect on service quality.…”
Section: Js and Sqmentioning
confidence: 99%